Power electronics laboratory theory, practice and organization - Arora, O.P (Narosa series in power and energy systems, 2007)
"Power Electronics Laboratory: Theory, Practice and Organization" provides an up-to-date and balanced coverage of all important power electronic devices including experiments on converters using new power electronic devices such as IGBTs, Power MOSFETs, etc. It will serve as a practical and necessary supplement to the main text for undergraduate, postgraduate and diploma students of electrical, electronics and telecommunication engineering. The book is also a rich source of information to instructors, teachers, manufacturers of Drives and laboratory incharges. It also provides relevant information for the development and organization of a well-equipped power electronics instructional laboratory.